Toward a More Advanced Village: Policy for Enhancing the Capacity of Village Apparatuses in Naru Village, Bima Regency - Rifai, Rifai (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study focuses on enhancing the capacity of Village Apparatuses in Naru Village, Bima Regency to improve their performance in executing Village Government duties. The aim of the study is to determine the effectiveness of capacity building programs for village officials. A descriptive quantitative research method was employed with a sample size of 30 respondents, representing a total population of 2,630 individuals who visited the Naru Village Office. The data was collected through a questionnaire and analyzed based on the respondents' answers. The study found that the role of the Village Government is critical in achieving predetermined targets, and most villages in Indonesia operate under customary law regulations. The study highlights the importance of having quality human resources with high work ethics and productivity to ensure optimal contributions to Village Government duties. Overall, this research contributes to the development of policies for enhancing the capacity of Village Apparatuses in Naru Village and other similar settings, towards creating welfare and development for the people in the village.